Sengketa Kepemilikan Hak Atas Tanah Di Kecamatan KaurSelatan - Indah Safitri; Herawan Sauni (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The relevance and benefits of land are very important for human survival, because this is a fundamental factor for human life. This can be seen from the large number of land settlements that we experienced in ancient times. These disputes are part of the social structure of all communities, although heredity manifests itself in different ways. This research uses an empirical legal research approach which is based on the use of primary and secondary data. Primary data was collected from analysis of conflicts related to overlapping property rights certificates. This information includes details about the parties involved, the circumstances surrounding the conflict, and the outcome of the resolution. Secondary Data isobtained from research available in the library, which serves as the basis for analysis. The study reveals that conflicts that occur in different communities include inheritance settlements, grants, and land sales. The elements that encourage the emergence of wider land conflicts include high economic value, increased public awareness, land availability with population growth, and poverty. Conflict resolution in society can be broadly classified into two ways, namely through the judicial process (litigation) and outside the judiciary (nonlitigation). The non-litigation settlement system that is often used by the community includes two methods, namely negotiation, where the settlement process involves interested parties byutilizing the help of a third party as a mediator (middleman) and a facilitation system, namely a settlement method that involves both parties to the dispute looking for a way out with the help of a facilitator.